Meningkatkan Kemampuan Menulis Melalui Metode Estafet Writing pada Siswa Kelas IV SD Inpres Teladan Merpati Kecamatan Bantaeng Kabupaten Bantaeng - Fauziah Nur Islamiah; Sitti Aida Azis; Syekh Adi Wijaya Latief (LPPM Politeknik Pratama, 2023)
The purpose of this study was to improve writing skills through the Writing Relay Method for fourth grade students of SD Inpres Teladan Merpati, Bantaeng District, Bantaeng Regency. This type of research was a Class Action Research which consisted of two cycles where each cycle was held in four meetings. Research procedures include planning, implementation of action, observation and reflection. The subjects in this study were 24 students in class IV of SD Inpres Teladan Merpati, Banateng District, Bantaeng Regency. In the second cycle, it was obtained that the average grade IV student learning outcomes of SD Inpres Teladan Merpati, Bantaeng District, Bantaeng Regency was higher, reaching 81.10. The learning completeness of fourth grade students at Teladan Merpati Inpres Elementary School, Bantaeng District, Bantaeng Regency has also increased. In cycle I, 6 (25%) students achieved learning mastery, while in cycle II as many as 22 (91.6%) students achieved learning mastery and classical learning mastery was achieved. This means that learning mastery in cycle II was achieved classically because the number of students who completed more than 80%.